Where is my neighborhood? A dynamic individual-based definition of home ranges and implementation of multiple evaluation criteria. (July 2017) - Hasanzadeh, Kamyar; Broberg, Anna; Kyttä, Marketta
Abstract: With the growing interest in studying characteristics of geographical context and its influence upon people, the concept of home range has been a focus of scholarly research. Home ranges are studied extensively across multiple disciplines, with literature supporting different operationalization techniques. This article argues that many of the existing approaches are not dynamic and versatile enough and do not provide reliable solutions for estimating individual home ranges. We additionally argue that many of current studies lack robust evaluation approaches. Recent evidences suggest that the usual approaches, which often exclusively rely on a single validation criterion, are not reliable and may be influenced by inferential errors. This study aims to tackle the exiting limitations in definition and operationalization of individual-based home range models and provide a more robust solution for their evaluation and comparison. Using data collected through public participation GIS we develop an applied, dynamic, and parametric model of individual home ranges. Subsequently, we propose multiple criteria comprising five validation hypotheses to evaluate model's effectiveness. We argue that application of this approach in evaluating spatial delimitation models can ameliorate the risk of biased validation resulting from inferential errors. The evaluation results indicate a substantial improvement in coverage of visited points compared to previously used static methods. Consequently, this paper draws a number of conclusions that can serve as guidelines for future research. This paper highlights the strengths and weaknesses of the proposed method and explains how it can be improved and employed in future studies investigating contextual effects on residents. Highlights: Investigates the limitations in neighborhood delimitation research. Presents an applied home range model using PPGIS data. Evaluates the efficiency of the model using novel criteria. Presents guidelines for future research.